Left Main Coronary Dissection in a Patient with Takayasu's Arteritis - İbrahim AKPINAR,; Muhammet Raşit SAYIN,; Turgut KARABAĞ,; Emrah KÜÇÜK,; Sait Mesut DOĞAN,; Mustafa BÜYÜKATEŞ,; Mustafa AYDIN1, (Archives of Rheumatology, 2013)
Takayasu's arteritis is a type of vasculitis which is characterized by chronic inflammation involving the aorta and its major proximal branches. The inflammatory process in the vessel wall due to intimal thickening and fibrosis may result in catastrophic events such as vascular stenosis and spontaneous dissection. However, spontaneous coronary dissection is a relatively rare outcome. The use of transthoracic echocardiography in the evaluation of thoracic aortic involvement has been shown to be advantageous since this method is relatively cheap and non-invasive. In this article, we report a 48-year-old female case who was previously diagnosed with Takayasu's arteritis with a spontaneous left main coronary artery dissection which was detected by coronary angiography following the sudden onset of severe chest pain.